Can Reforming Dismissal Procedures in State Administrative Courts Enhance Transparency and Accountability? - Ashilsyah, Maulidhiyo Aprarel; Nuriyatman, Eko; Rodiyah, Rodiyah; Wedhatami, Bayangsari (Indonesian State Law Review, 2024)
The effectiveness of Indonesia’s State Administrative Courts is increasingly under scrutiny, particularly regarding the dismissal procedures that often lack transparency and accountability. This research explores the urgent need for reform in these procedures to foster greater public trust in the judicial system. In a country where citizens’ rights and access to justice are vital to democratic governance, the lack of clarity and fairness in dismissal decisions can undermine confidence in the court’s integrity. The novelty of this study lies in its focus on dismissal procedures as a critical yet often overlooked area of judicial reform. By examining current practices, legal frameworks, and case law, the research identifies key weaknesses in the system, proposing innovative reforms aimed at enhancing procedural transparency, consistency, and accountability. A comparative analysis with international best practices highlights practical solutions that could be adopted to improve the fairness and efficiency of dismissal processes. This research makes a significant contribution by offering a targeted framework for reform that prioritizes the protection of citizens’ rights, ensuring that judicial decisions, particularly dismissals, are made with clarity, fairness, and public scrutiny. It calls for systemic change to align administrative justice with democratic principles of openness and accountability.